ChemInform Abstract: Stabilization of Cubic Sr2FeMoO6 Through Topochemical Reduction. Issue 39 (September 2015) - Taylor, Daniel D.; Schreiber, Nathaniel J.; Brown, Craig M.; Arevalo‐Lopez, Angel M.; Rodriguez, Efrain E.
Abstract A reduced form of Sr2FeMoO6 is synthesized through topochemical reduction with CaH2 (glass ampule, 500 °C, 3 d).